Full Tilt - Shusterman, Neal. (New York : Simon & Schuster Books for Young Readers, 2003)
When sixteen-year-old Blake goes to a mysterious, by- invitation-only carnival he somehow knows that it could save his comatose brother, but soon learns that much more is at stake if he fails to meet the challenge presented there by the beautiful Cassandra.
700L
Accelerated Reader/Renaissance Learning
Accelerated Reader AR
Keywords: Carnivals; Juvenile fiction; Brothers -- Juvenile fiction; Self-perception -- Juvenile fiction; Near-death experiences; Juvenile fiction; Carnivals; Fiction; Brothers -- Fiction; Self-perception; Fiction; Near-death experiences; Fiction; Horror stories; Fiction